2012
DOI: 10.1002/ijc.27429
|View full text |Cite
|
Sign up to set email alerts
|

Low values of 5‐hydroxymethylcytosine (5hmC), the “sixth base,” are associated with anaplasia in human brain tumors

Abstract: 5-Methylcytosine (5mC) in genomic DNA has important epigenetic functions in embryonic development and tumor biology. 5-Hydroxymethylcytosine (5hmC) is generated from 5mC by the action of the TET (Ten-Eleven-Translocation) enzymes and may be an intermediate to further oxidation and finally demethylation of 5mC. We have used immunohistochemistry (IHC) and isotope-based liquid chromatography mass spectrometry (LC-MS) to investigate the presence and distribution of 5hmC in human brain and brain tumors. In the norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
142
3
15

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 143 publications
(175 citation statements)
references
References 24 publications
15
142
3
15
Order By: Relevance
“…On the other hand, 5-hmC was reduced by about 3-fold in the tumors of GC cases. In line with recent studies [9,26], our data also show that 5-hmC values varied widely among individuals. P values were analyzed using a two-tailed Pearson correlation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, 5-hmC was reduced by about 3-fold in the tumors of GC cases. In line with recent studies [9,26], our data also show that 5-hmC values varied widely among individuals. P values were analyzed using a two-tailed Pearson correlation.…”
Section: Discussionsupporting
confidence: 93%
“…and 2-oxoglutarate (2-OG), and 2-OG is dependent on the activity of isocitrate dehydrogenase IDH1 and IDH2 [5,6] ( Figure S1). The loss of 5-hydroxymethylcytosine and the down-regulation of the TET family and IDH2 have been found in human cancers [7][8][9][10][11], but comprehensive evaluations of the modified cytosines and the enzymes that are involved have remained largely unperformed and most previous studies have used dot blot analyses as a means of measuring 5-hydroxymethyldeoxycytidine (5-hmC), which is at best a semi-quantitative method. Because dot blot analysis is based on the antigen-antibody reaction direct assessments of the absolute amount of 5-mC, 5-hmC, 5-fC, and 5-caC are not possible.…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al showed tumor-associated loss of 5hmC for lung, brain, breast, liver, kidney, prostate, intestine, and uterus cancers and melanoma [109]. Reduction of 5hmC in different types of solid tumors was confirmed in many other studies [110][111][112][113][114]. Although decreased 5hmC seems to be a common feature of cancers, there is no straight link with TET expression or Brought to you by | MIT Libraries Authenticated Download Date | 5/11/18 7:43 PM mutation levels and aberrant methylation.…”
Section: Ogt and Tetmentioning
confidence: 87%
“…The conversion of 5mC to 5-hydroxy-methylcytosine (5hmC) in mammalian cells by methylcytosine dioxygenase Ten-Eleven Translocation (TET) is thought to be an important procedure during active demethylation process [23]. 5hmc has been recognized as the "sixth base" in the genome because of its distinctive epigenetic role [24].…”
Section: Dna Methylation and Demethylationmentioning
confidence: 99%
“…Brain is one of the organs that with 5hmC presence at high levels. In terms of cancers developed in the central nervous system, it is observed that 5hmC levels decreased by clinical grades of the tumors; meaning high numbers of 5hmC positive cells in WHO grade I gliomas, fewer in grades II and III, and the least number of 5hmC positive cells in grade IV gliomas [24,45].…”
Section: Biological Impact Of Dna Hypomethylation In Cancer Developmentmentioning
confidence: 99%